The revolutionary woman in Human Cannon by Edward Bond: Agustina de Estarobon (Philologia, 2021)
This article proposes a detailed analysis of the play Human Cannon, by the English author Edward Bond, with a special emphasis on the female ﬁgure who becomes a historical spokeswoman of the Spanish Civil War. As a consequence of the scenic methodology approached in this study, the development of the protagonist, Agustina de Estarobon, can be followed from the initial subjugation to the political maturity and freedom of thought at the end of the play. In this way, Edward Bond exempliﬁes a heroine brave enough to face the fascist repression and lead a rebellion against the injustices of absolute power.